Gastro-intestinal nematodes of the zebu calves on native pasture in the Pantanal Region, Brazil. I. Prevalence, intensity of infection and seasonal variation - Catto, João Batista; Ueno, Hakaru (Pesquisa Agropecuaria Brasileira, 2014)
From May 1976 to June 1978, an epidemiological study on gastro-intestinal nematodes of the Zebu calves on native pasture, was carried out in the Pantanal region, Brazil. Haemonchus, Oesophagostomum and Cooperia were the most common genus with high prevalence. Ninety-five percent of total number of Haemonchus collected were identified as Haemonchus similis. Faecal egg counts varied greatly from season to season during the experiment period. On the whole, the counts reflected the fluctuations of worm burden. The counts, however, did not always reveal the degree of infection with gastro-intestinal parasites. It was proved that Haemonchus spp. was the most predominant in the larval identification, but Cooperia spp. was more abundant than Haemonchus in the worm burden. The relationship between the intensity of infection of the calves with the gastro-intestinal parasites and climate factors, such as temperature, precipitation and evapotranspiration, was analized. The results showed that the monthly water deficiency on the soil or its surplus had a closed correlation with the dynamic populations of the nematode parasites.